Psychosocial Predictors of Glaucoma Medication Adherence among the Support, Educate, Empower (SEE) Personalized Glaucoma Coaching Pilot Study Participants - Salman, Mariam (Am J Ophthalmol, 2020)
PURPOSE: To evaluate the association between baseline psychosocial milieu and subsequent glaucoma medication adherence among participants in the Support, Educate, Empower (SEE) personalized glaucoma coaching program pilot study. DESIGN: Prospective cohort study. PARTICIPANTS: University of Michigan glaucoma patients ≥ age 40, taking ≥ 1 glaucoma medication, who self-reported poor adherence. METHODS: Participants completed a baseline survey that assessed: 1) Demographics; 2) Social network; 3) Perceived Stress; 4) Consideration of future consequences; 5) Glaucoma-related distress and 6) Social support. Medication adherence was then monitored electronically (AdhereTech, New York, NY) for 3 months and the percentage of prescribed doses taken was calculated. The relationship between baseline factors and medication adherence was assessed using univariate and multivariate analysis. MAIN OUTCOME MEASURES: Median percent adherence over three months. RESULTS: Of the 95 study participants, 63% had graduated from college, 55% were white, 35% were African-American, and 97% had insurance. Median adherence over three months was 74% ± 21% (± standard deviation, SD). Higher income and more education were significantly associated with better adherence (p<0.0001, p = 0.03). Glaucoma related distress (mean score 5.6, SD = 3.0) was inversely associated with medication adherence on univariate (p<0.0001) and multivariate analysis (p=0.0002). Every one-point increase in glaucoma related distress score predicted a 2.4 percentage-point decrease in medication adherence. CONCLUSIONS: Lower income, lower educational attainment and a higher level of glaucoma-related distress all predicted lower adherence to glaucoma medications. Additional glaucoma self-management support resources should be directed towards patients with such risk factors for poor adherence.